A life cycle thinking-based environmental risk framework for screening sustainable feedstocks in early-stage bioeconomy projects - George Bishop; Carmen Girón-Domínguez; James Gaffey; Maeve Henchion; Réamonn Fealy; Jesko Zimmermann; Wriju Kargupta; David Styles (Resources, Environment and Sustainability)
Understanding the environmental impacts of bio-based feedstock production is essential for sustainable bioeconomy development. Consequential life cycle assessment (LCA) evaluates environmental sustainability, often identifying “hidden” impacts incurred through market displacements. However, it is often impractical to screen multiple bioeconomy feedstocks and value chains using full consequential LCA early in project conceptualisation, owing to high requirements in terms of time, data, and expertise. As a result, critical environmental risks may not be discovered until too late in project development to redirect investment towards more sustainable options. This paper introduces the Bio-based feedstock Environmental Risk Assessment (Bio-ERA) Framework, designed to support early screening of potential upstream environmental risks associated with increased demand for bio-based feedstocks. The Bio-ERA Framework comprises a decision tree that systematically guides stakeholders through consequential life cycle thinking, elucidating sometimes hidden (indirect) pathways of impact among feedstock sourcing decisions. Seven important environmental aspects are addressed: Finite Resource Inputs, Greenhouse Gas (GHG) Emissions, Air Quality, Water Quality, Ecosystem Diversity, Terrestrial Carbon Storage, and Indirect Land Use Change. Criteria are proposed to structure evaluation of (i) probability and (ii) severity of environmental impact, in relation to four categories of feedstock: primary (determining product), high-value by-product, low-value by-product, and waste. Example applications demonstrate how the framework can generate an environmental risk profile for specific feedstocks sourced in specific contexts. Bio-ERA does not avoid the need for detailed LCA evaluation of full bioeconomy value chains, but promotes deeper interrogation and awareness of potential environmental risks associated with feedstock sourcing, in a manner that is accessible to all stakeholders. This could support earlier screening of strategic investment decisions necessary to develop a sustainable bioeconomy.